Promoting female condoms in the sex industry in 4 towns of Southern China: context matters. - Nie, Li; Liao, Susu; Weeks, Margaret R; Wang, Yanhong; Jiang, Jingmei; Zhang, Qingning; Zhou, Yuejiao; He, Bin; Li, Jianghong; Dunn, Jennifer (Sexually transmitted diseases, 2013)
The female condom (FC) is an effective tool for dual protection, but it remains underused. Individual and contextual reasons need to be explored.
Keywords: Adolescent; Adult; China; Condoms, Female; Cross-Sectional Studies; Female; Health Education; Health Knowledge, Attitudes, Practice; Health Promotion; HIV Seropositivity; Humans; Male; Middle Aged; Sex Workers; Sexual Behavior; Sexually Transmitted Diseases